2019
DOI: 10.1158/0008-5472.can-18-3190
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1—No Matter How You Splice It

Abstract: BRCA1 (breast cancer 1, early onset), a well-known breast cancer susceptibility gene, is a highly alternatively spliced gene. BRCA1 alternative splicing may serve as an alternative regulatory mechanism for the inactivation of the BRCA1 gene in both hereditary and sporadic breast cancers, and other BRCA1-associated cancers. The alternative transcripts of BRCA1 can mimic known functions, possess unique functions compared with the full-length BRCA1 transcript, and in some cases, appear to function in opposition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 133 publications
(190 reference statements)
0
24
0
Order By: Relevance
“…Despite advances in treatment strategies involving surgery, radiotherapy, chemotherapy, endocrine therapy, and targeted therapy, patients with breast cancer still have a poor prognosis (3, 4). To date, it has been demonstrated that many molecules, such as BRCA1 (breast cancer susceptibility gene 1), HER2 (human epidermal growth factor receptor 2), and p53, are involved in the occurrence and development of breast cancer (57). However, the underlying mechanisms for breast cancer especially regarding its tumorigenesis remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in treatment strategies involving surgery, radiotherapy, chemotherapy, endocrine therapy, and targeted therapy, patients with breast cancer still have a poor prognosis (3, 4). To date, it has been demonstrated that many molecules, such as BRCA1 (breast cancer susceptibility gene 1), HER2 (human epidermal growth factor receptor 2), and p53, are involved in the occurrence and development of breast cancer (57). However, the underlying mechanisms for breast cancer especially regarding its tumorigenesis remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although the smaller isoforms may, in part, compensate for the lack of a full-length BRCA1 protein (cf. review [52]—with p53 brought into perspective—and as indicated, in relation to therapeutic resistance in cell experiments highlighting Δ11q [46]), they also have unique functions, some in opposition to full-length BRCA1, and a balanced splicing profile seems to be important for the normal physiological function of BRCA1 (reviewed in [53]). Last year, pathogenic BRCA1 mutations were identified in the homozygous state in four children with multiple congenital anomalies and severe chromosomal fragility; these mutations notably resulted in the absence of a full-length BRCA1 transcript, but in the presence of Δ11q [54].…”
Section: Introductionmentioning
confidence: 99%
“…It shows sequence-nonspecific (damaged) DNA binding [59,60,61,62] and has many protein partners. Figure 1 (collecting information from reviews [53,57,63,64] and references therein, plus [60,61,62,65,66,67,68,69,70,71]) attempts to give an idea of the switches and plug-ins on the BRCA1 protein that could be specific to a given isoform, highlighting attributes relevant to exon 11. The properties rely inter alia on protein conformation, and are thus not directly predictable from the illustration; as an example, BRCA1-IRIS contains the RING domain but, unlike full-length BRCA1, it seems unable to bind to BARD1 [44].…”
Section: Introductionmentioning
confidence: 99%
“…The product of a BReast CAncer Type 1 ( BRCA1 ) gene controls the cell cycle and ensures DNA repair. Mutation in the BRCA1 gene leads to BC predisposition due to the loss of a gene function [ 61 ].…”
Section: Nanomaterials/nanoparticles-based Electrochemical Biosensmentioning
confidence: 99%